The Effect of Store Atmosphere (Store Mobile) and Location on Consumer Buying Interest In Building Store Sumber Intan In – Pulo Ampel District - Adiyanto, Yoga (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2021)
This study aims to determine the effect of Store Atmosphere (Store Atmosphere), Location on Consumer Buying Interest at the Sumber Intan Building Store in Pulo Ampel District. The research was conducted using a survey method, the sample used was 100 respondents using accidental sampling. The study was conducted at the Sumber Intan Store from April 23 to July 17, 2019. Data were collected using a questionnaire and analyzed using SPSS version 24. Based on the results of the study, it can be concluded that: 1) there is a significant effect between Store Atmosphere and Interests Consumer Buying, 2) there is a significant influence between Location and Consumer Buying Interest, and 3) there is a significant influence between Store Atmosphere (Store Atmosphere) and Location on Consumer Buying Interest.